Mystical Kinship of Creation: A Foundation of Ecospirituality for Interreligious Ecological Movements - Stefanus Christian Haryono (International Journal of Indonesian Philosophy & Theology, 2021)
This article explores the intersection between Bhumi Devi in Hindu Mythology and the Canticle of Creation of Saint Francis of Assisi. This intersection discovers the concept of the mystical kinship of creation as a foundation of ecospirituality. The exploration which is rooted in two different traditions, Hinduism and Christianity, enlightens interreligious ecological movements that they need not only action but also a spiritual foundation.